2005
DOI: 10.1038/sj.bjc.6602868
|View full text |Cite
|
Sign up to set email alerts
|

Overall obesity, abdominal adiposity, diabetes and cigarette smoking in relation to the risk of pancreatic cancer in two Swedish population-based cohorts

Abstract: We examined the associations of body mass index (BMI), waist circumference, a history of diabetes, and cigarette smoking with risk of pancreatic cancer among 37 147 women and 45 906 men followed up during 560 666 person-years in the Swedish Mammography Cohort and the Cohort of Swedish Men; 136 incident cases of pancreatic cancer were diagnosed. The multivariate rate ratio (RR) of pancreatic cancer for obese women and men (BMI X30 kg/m 2 ) was 1.81 (95% CI: 1.04 -3.15) compared to those with a BMI of 20 -25 kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
110
5
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(136 citation statements)
references
References 26 publications
11
110
5
10
Order By: Relevance
“…Since 2000, at least 13 prospective cohort studies carried out in Western countries have reported a link between BMI and pancreatic cancer risk, 6,10,[15][16][17][18][19][20][21][22]26,35 although the findings have been inconsistent. In studies carried out in the U.S.A., a positive relationship was demonstrated for both men and women in the 3 largest cohort studies, [15][16][17] while 4 other smaller studies found a positive association only in men.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Since 2000, at least 13 prospective cohort studies carried out in Western countries have reported a link between BMI and pancreatic cancer risk, 6,10,[15][16][17][18][19][20][21][22]26,35 although the findings have been inconsistent. In studies carried out in the U.S.A., a positive relationship was demonstrated for both men and women in the 3 largest cohort studies, [15][16][17] while 4 other smaller studies found a positive association only in men.…”
Section: Discussionmentioning
confidence: 92%
“…In studies carried out in the U.S.A., a positive relationship was demonstrated for both men and women in the 3 largest cohort studies, [15][16][17] while 4 other smaller studies found a positive association only in men. 10,22,26,33 The 6 other studies, including the 2 largest European cohort studies, 6,[18][19][20][21]35 did not find any significant association in the combined data of men and women. Similar to cohort studies, case-control studies have also produced contradictory results with a meta-analysis carried out in 2003 concluding that the risk of pancreatic cancer was only weakly associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, several studies present results showing an increased risk of pancreatic cancer with increasing BMI,13, 21, 22, 23 which has not been observed in the MDCS, neither in men nor in women 42. Still, adipose tissue is also known to produce estrogens, thus suggesting it may play a protective role as well.…”
Section: Discussionmentioning
confidence: 93%
“…Tobacco smoking,4, 5, 6 high age4, 7, 8 and heredity9, 10 seem to be the only truly validated risk factors for pancreatic cancer. Several other risk factors have been investigated, and numerous studies claim a significant impact of diabetes,11, 12, 13 pancreatitis,14, 15, 16 alcohol17, 18, 19, 20 and body mass index (BMI)13, 21, 22, 23; however, no consensus has yet been reached.…”
mentioning
confidence: 99%
“…Studies have implicated obesity, lack of exercise, dietary glycemic load (an estimation of post-prandial glucose response), and diabetes mellitus as risk factors for pancreatic cancer (Gapstur et al, 2000;Michaud et al, 2001Michaud et al, , 2002Eberle et al, 2005;Huxley et al, 2005;Larsson et al, 2005). The mechanisms by which these factors increase cancer risk have been hypothesized to involve insulin and the insulin-like growth factor axis, which are intimately involved in glucose and energy homeostasis (Kaaks and Lukanova, 2001;Jerome et al, 2003).…”
Section: Discussionmentioning
confidence: 99%